Eating Patterns, Physical Activities with the Event of Obesity Based on Waist-Hip Circumstances Ratio - Yuli Rahmadani; Tri Ardianti Khasanah (Sarana Ilmu Indonesia (salnesia), 2023)
Obesity is a chronic health problem caused by various multifactorial factors, such as genetic factors, environmental factors, inappropriate eating behavior and low physical activity. The research aims to analyze the relationship between eating patterns and free time physical activity with the incidence of obesity based on the waist-hip circumference ratio in Jakarta Lantamal III Health Service personnel. The research is a quantitative study with a cross-sectional design. A total of 66 subjects who met the inclusion criteria and agreed to informed consent underwent anthropometric measurements and filled out questionnaires. Dietary pattern data uses the food frequency questionnaire (FFQ) form, leisure time physical activity data is taken using the Godin leisure time exercise questionnaire (GLTEQ). The data were analyzed using the Chi-Square test. 54,5% of research subjects were obese, 63,6% of subjects had a good diet, and 56,1% of subjects rarely consumed food sources of fiber. and subjects with light leisure time physical activity category, namely 42,4%. It was found that 83,8% of research subjects who rarely consumed fiber had obese nutritional status and 96,4% of research subjects who had light free time physical activity had obese nutritional status. The results of bivariate statistical analysis showed that there was a significant relationship between the frequency of consumption of food sources of fiber and activity. physical leisure time with the incidence of obesity (p-value<0,05). So, it can be concluded that low fiber consumption and reduced levels of physical activity can increase the incidence of obesity.